1994
DOI: 10.1037/0022-006x.62.3.543
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of cognitive-behavioral and brief psychodynamic psychotherapies for depressed family caregivers.

Abstract: Clinically depressed family caregivers (N = 66) of frail, elderly relatives were randomly assigned to 20 sessions of either cognitive-behavioral (CB) or brief psychodynamic (PD) individual psychotherapy. At posttreatment, 71% of the caregivers were no longer clinically depressed according to research diagnostic criteria (RDC), with no differences found between the 2 outpatient treatments. The results suggested therapy specificity; there was an interaction between treatment modality and length of caregiving on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
88
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(92 citation statements)
references
References 25 publications
3
88
0
1
Order By: Relevance
“…12,13 Although the two approaches were similar in the sense that they both aim at thought modification, our approach, though providing a background about the thought-emotion-behavior maintenance cycle and the role of dysfunctional beliefs in engendering negative emotions, does not attempt to tackle person-specific dysfunctional beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Although the two approaches were similar in the sense that they both aim at thought modification, our approach, though providing a background about the thought-emotion-behavior maintenance cycle and the role of dysfunctional beliefs in engendering negative emotions, does not attempt to tackle person-specific dysfunctional beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is generally assumed that depressive disorders can be treated adequately in many cases, both with psychological (Churchill et al, 2001) and pharmacological (Anderson, 2001;Thase, 2003) interventions. And intervention studies have shown that major depression in caregivers can be treated effectively (Adkins, 1999;Gallagher-Thompson & Steffen, 1994;Lovett & Gallagher, 1988). As the number of caregivers of dementia patients will increase considerably over the next decades, it is important to assess the prevalence and incidence of depressive disorders in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, variações nos resultados têm sido apontadas quando levamos em consideração as características individuais dos pacientes, como tempo de doença, comorbidades, traços de personalidade, severidade, diagnóstico psiquiátrico, existência de foco, qualidade das relações de objeto, funcionamento defensivo, estado civil, entre outros. Esses resultados, porém, ainda são incipientes, e não há um consenso que permita definir qual o tipo de tratamento mais adequado para um paciente em particular, a partir de evidências científicas [1][2][3][4][5][6][7][8][9] . Diversos autores vêm confrontando o mito de que todos os pacientes podem ser tratados e curados com psicoterapia de orientação analítica, ou análise, como um equívoco que pode desacreditar a técnica e levar a gastos e sofrimentos desnecessários 10 .…”
Section: Introductionunclassified